New Record of some Cyperaceae Taxa in India - Naithani, H. B.; Raizada, M. B. (Indian Forester, 1977)
The paper presents a new combination i.e. Fimbristylis falcata (Vahl) Kunth var. latifolia (Kunth) Naithani et Raizada and new records of J3 taxa of sedges (Cyperaceae) in India, viz. Cyperus sanguinolentus Vahl ssp. melanocephalus (Miq.) Kern, Fimbristylis falcata Kunth var. latifolia (Kunth) Naithani et Raizada comb nov., Scleria corymbosa Roxb. for North India; Cyperus unioloides R. Br., Fimbristylis salbundia (Nees) Kunth, Fimbristylis stolonifera C. B. Clarke for Central India; Scleria biflora Roxb. for Madhya Pradesh; Cyperus melanospermus (Nees) Valk-Sur., Fimbristy1is pierotii Miq, Scleria rugosa R. Br. for Orissa; Cyperus pulchellus R. Br. for Orissa and Gujarat; Fimbristylis sieberiana Kunth for North & South, India and Fimbristylis velata R. Br. for Karnataka. Notes on synonomy, short description, distribution and distinction from allied species are provided, species are arranged alphabetically. All specimens quoted are deposited in Dehra Dun Herbarium (DD).